Evaluation of parallel MRI techniques - Sakinah Saaban. (2010)
Parallel magnetic resonance imaging has turned out to be one of the most important recent developments in MR imaging, impacting examination protocols in virtually all areas of research imaging and clinical MRI. Although there is an enormous amount of publications on different reconstruction and processing techniques, little effort has been made to make these tools accessible. Image quality in parallel MRI depends on various factors, such as receiver coil array configuration, reduction factor, k-space coverage and the method of reconstruction. Here we will analysis the different types of MRI available. We will base on some case studies and research. The case studies that are being referenced upon are the abdomen imaging and knee imaging. We will also do some simulation on MATLAB using the pulsar toolbox that is available for the different types of imaging namely, GRAPPA, PILS, SMASH and SENSE. A brief overview and their advantages and disadvantages will also be stated to help in choosing the optimal parallel imaging method for a specific clinical application. In general, most modern MRI methods will result in similar image quality for most applications, while some specific application may benefit from specialized MRI approaches. However, it is clear that MRI methods have the potential to impact nearly every area of clinical MRI.